Pencapaian Keluarga Sakinah melalui Pemberdayaan Ekonomi di Desa Buddagan Kecamatan Pademawu - Erie Hariyanto; Maimun Maimun; Ainurrahman Hidayat (PERDIKAN (Journal of Community Engagement), 2020)
The number of divorce cases in Indonesia, child abuse, violence, and criminal acts in the household are proof that in realizing the Sakinah family requires the involvement of several parties; parents, the Religious Affairs, and the village government. This community service theme has a correlation with the District Office of Religious Affairs (KUA) in Pademawu District, Pamekasan Regency. The functions and duties were to deal with quite complex issues concerning all religious matters including marriage, divorce, divorce, reconciliation. "Achievement of Sakinah Families through Economic Empowerment in Buddagan Village, Pademawu District". The study is intended to minimize divorce and early marriage cases in Pademawu community, especially in Buddagan. Economic factors are one important factor in navigating the Sakinah family. The need for solid cooperation between parents, the community, and the KUA in order to strengthen the Sakinah family in various aspects including Economy, Education, and Culture. In the field of economic empowerment, it is necessary to involve the local government and the government of the province of East Java to support capital and job training.(Banyaknya kasus perceraian di Indonesia, terjadinya pelecehan anak, kekerasan dan tindak kriminal dalam rumah tangga adalah bukti bahwa dalam mewujudkan keluarga sakinah butuh keterlibatan beberapa pihak. Seperti orang tua, KUA dan pemerintah desa menjadi komponen yang penting dalam membentuk keluarga sakinah mawadah warahmah. Tema Pengabdian kepada masyarkat ini memiliki korelasi dengan Kantor Urusan Agama Kecamatan (KUA) di Kecamatan Pademawu Kabupaten Pamekasan. Adapun fungsi dan tugasnya waktu itu adalah menangani persoalan yang cukup kompleks mengenai seluruh urusan keagamaan termasuk didalamnya adalah Nikah, Talak, Cerai, Rujuk. “Pencapaian Keluarga Sakinah Melalui Pemberdayaan Ekonomi di Desa Buddagan Kecamatan Pademawu”. Adapun tujuan penyuluhan ini ialah untuk mengurangi adanya perceraian dan pernikahan dini oleh masyarakat pademawu khususnya masyarakat Buddagan. Faktor ekonomi menjadi salah satu faktor terpenting dalam mengarungi keluarga sakinah kedepan. Perlunya kerjasamanya yang padu antara orang tua, masyarkat dan KUA dalam rangka memperkuat keluarga sakinah dalam berbagai aspek diantaranya Ekonomi, Pendidikan dan Budaya. Dalam bidang pemberdayaan ekonomi perlu keterlibatan pemerintah daerah dan pemerintah propensi jawa timur untuk mendukung permodalan, pelatihan kerja).